An extension to l-calculus for Distributed Functional Actor Programming - Najat, Rafalia; Abouchabaka, Jaafar (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
In this paper, we present the lAD-calculus witch is an elementary functional distributed actor language with a new approach of message communication between actors in a distributed environment. This strategy is based on a static analysis which allows determining the parts of a message that must be transmitted. The actors we consider have a functional script and manipulate the terms of the lAD-calculus. The expressions of this language correspond to those of the l-calculus extent by some actor primitives.